Mediating role of self-efficacy in the relationship between family functioning and self-management behaviors in patients with coronary heart disease: A cross-sectional study in Jiangsu, China - Wang, Yang; Masingboon, Khemaradee; Wacharasin, Chintana (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Self-management behaviors can prevent the negative consequences among patients with coronary heart disease (CHD). The reality of patients followed the self-management behaviors rate are unoptimistic. Objective: This study aimed to examine whether self-efficacy serves as a mediating role between family functioning and self-management behaviors among coronary heart disease patients. Methods: A cross-sectional approach was applied, and 140 patients with CHD were included using a cluster sampling strategy. Family functioning was assessed utilizing the Family APGAR Index, self-efficacy was evaluated using the Self-efficacy for Chronic Disease 6-item Scale, and self-management behaviors was examined utilizing the Coronary Artery Disease Self-Management Scale. Data were collected from July to October 2022 and analyzed using descriptive statistics and regression analyses to evaluate the mediating influence. Results: The degree of self-management behaviors among patients with CHD was at a low level (Mean = 82.23, SD = 11.863). Self-efficacy had a direct and positive impact on self-management behaviors (β = 0.39, p <0.001). Moreover, self-efficacy had a partially intermediary function in the relationship between family functioning and self-management behaviors (indirect effect = 0.14, 95% CI [0.04, 0.27]; direct effect = 0.39, p <0.001). Conclusion: Self-efficacy demonstrated an association with self-management behaviors and served as a mediation function in the relationship between self-management behaviors and family functioning. Therefore, the significance of family functioning and self-efficacy should be highlighted in nursing practice when developing methods to encourage patients with CHD to improve their self-management behaviors.